Waddington’s Landscapes in the Bacterial World - Sánchez-Romero, María A.; Casadesús, Josep (Frontiers in Microbiology, 2021)
Conrad Waddington's epigenetic landscape, a visual metaphor for the development of multicellular organisms, is also appropriate to depict the formation of phenotypic variants of bacterial cells. Examples of bacterial differentiation that result in morphological change have been known for decades. In addition, bacterial populations contain phenotypic cell variants that lack morphological change, and the advent of fluorescent protein technology and single cell analysis has unveiled scores of examples. Cell-specific gene expression patterns can have random origin or arise as a programmed event. When phenotypic cell-to-cell differences are heritable, bacterial lineages are formed. The mechanisms that transmit epigenetic states to daughter cells can have strikingly different levels of complexity, from the propagation of simple feedback loops to the formation of complex DNA methylation patterns. Game theory predicts that phenotypic heterogeneity can facilitate bacterial adaptation to hostile or unpredictable environments, serving either as a division of labor or as a bet-hedging that anticipates future challenges. Experimental observation confirms the existence of both types of strategies in the bacterial world.